Effects of special nanoparticles on fuel cell properties of sulfonated polyethersulfone membrane - Sriram, K. (Taylor & Francis Inc, 2016)
Polyethersulfone was sulfonated by changing the reaction time with sulfuric acid. The degree of sulfonation and ion exchange capacity were determined. Sulfonation of polyethersulfone was confirmed by FT-IR analysis and a new peak at 1025 cm-1. Inorganic materials such as carbon nanotubes, graphene, and kaolinite nanoparticles were synthesized. The effects of three nanoparticles on thermal stability and water uptake of sulfonated polyethersulfone were investigated. The morphology of membranes were also altered due to the addition of inorganic materials. The proton conductivity of the modified membranes increased with respect to increase in relative humidity.